HUBUNGAN KEKREATIFAN GURU PAK DENGAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 1 SIGUMPAR KECAMATAN SIGUMPAR KABUPATEN TOBASA TAHUN PEMBELAJARAN 2017/2018 - Lestarina Lumban Gaol (IAKN Tarutung, 2018)
Abstract, This study aims to find out how the relation of creative teachers of Christian Religious Education with the motivation of studying students of class VIII SMP Negeri 1 Sigumpar Year of learning 2017/2018. The research hypothesis is: there is a positive and significant correlation of teacher's teacher's creativity with the motivation to learn the students of grade VIII SMP Negeri 1 Sigumpar Year of learning 2017/2018. This research is a correlational research using descriptive and imperative statistical techniques. The population is all students of class VIII SMP Negeri 1 Sigumpar 2017/2018 years of study that is Christian Protestant amounted to 137 people. Samples is 34 people. The research instrument is a closed questionnaire. The result of rx value = 0,468 rtabel = 0,339. Hypothesis test obtained t count = 2.995 ttable = 2.042 then H0 rejected and Ha accepted indicates that there is a positive and significant correlation of teacher Christian Education teacher's creativity with the motivation to study the students of grade VIII SMP Negeri 1 Sigumpar Learning year 2017/2018. The researcher concludes that the Creativity of Christian Religious Education teacher can support student's learning motivation. In connection with the results of this study. the authors provide input for the observer of the Christian Religious Education teachers to improve the creative in teaching so that student learning motivation can increase.